EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK DALAM PENINGKATAN SELF REGULATED LEARNING SISWA PENGGUNA GAME ONLINE - Eka Septia Warni; Firman Firman (Universitas Negeri Padang, 2020)
Online game users among adolescents today tend to increase and not infrequently this condition makes self-regulation in learning begin to be disrupted. Group tutoring has already taken place in schools and is rarely used to improve self-regulated learning. This study aims to look at the effectiveness of group guidance services in improving self-regulated learning of students using online games. This research uses a quantitative approach, with the Experiment method. Students who use online games are the subject of research. Data collection techniques are self regulated learning questionnaires. Data were analyzed using the Wilcoxon Signde Ranks Test. Based on the results of the study found that group guidance services can improve self-regulated learning of online game users. This finding has implications for guidance and counseling teachers in improving self-regulated learning of online game users through group guidance services.